Answer:
![(2(x-1)(2x+9))/((x-3)(x-2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/z9vropoodaelic5h0qt3bebsj2uwumnics.png)
Explanation:
![(4x)/((x-3))+(6)/((x+2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/pv6m4551he2qh6o1vqj6jslgn5ai6zarop.png)
=
Now we have done the denominators of each term of the expression equal.
Further we add the terms,
![(4x(x+2))/((x-3)(x+2))+(6(x-3))/((x+2)(x-3))](https://img.qammunity.org/2021/formulas/mathematics/high-school/4mikhte6slp7ly1cj9py8d3oxw8xkoq6lf.png)
=
![(4x(x+2)+6(x-3))/((x-3)(x+2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/c8oaiivtr8nx3r1paehf3kl94u8gnet4qz.png)
=
![(4x^(2)+8x+6x-18)/((x-3)(x+2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/t91rio3d012f2inso6tvqjwilv15w9j0b8.png)
=
![(4x^(2)+14x-18)/((x-3)(x-2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/nveevy3ctvuxd9r60o605226drzpik9mwr.png)
Now factorize the numerator of the fraction.
4x² + 14x - 18 = 2(2x² + 7x - 9)
= 2(2x² + 9x - 2x - 9)
= 2[x(2x + 9) - 1(2x + 9)]
= 2(x - 1)(2x + 9)
Therefore,
will be the answer.